Mastering the power of you : empowered by leader insights - Johri, Lalit M.; Corich, Katherine; Haskins, Gabrielle (Abingdon, Oxon ; New York, NY : Routledge, 2023)
"The world of the 2020s is complex and challenging. We are faced with a myriad of difficult decisions about our present and future, driven by the impact of the Covid19 pandemic, the economic downturn, rising unemployment and inequalities, digital disruption, uncertain political environments, and climate change. Many bright young people find themselves without work or diminishing hope of doing meaningful work. Similarly, the existing workforce is under pressure to diversify their skills or face the threat of losing their employment. Decision makers are struggling to meet urgent demands to reshape their organisations and to face the present and future successfully. In this book, leaders from around the world share their experiences in adapting to the changing world and the lessons they have learnt. They offer advice on how you can master a diverse range of leadership concepts and skills to prepare yourself for the 21st century world. The simple and easy-to-follow format of each chapter (grouped around the core concepts of Leadership, Entrepreneurship and Volunteering; Purpose and Values; Authenticity, Trust and Presence; Strategising, Thinking and Decision Making; Mentoring and Development; Mental Resilience; Diversity and Inclusion; Negotiating and Collaborating; and Social and Environmental Impact) will inspire you to master these concepts, skills and behaviours and use them to open new opportunities in your life and workplace. You will be taken on an expedition of discovery, guided by insights, with chapters on a wide range of 'powers' such as "the power of mental fitness", "digital entrepreneurship", "leadership", "purpose", "creative thinking", "kindness", and "sustainability". The nature of each power is revealed as each chapter unfolds, helping you to recognise and develop a broader set of skills and attributes, vitally important to thrive in today's workplace and world. If you are a recent graduate aspiring to gain meaningful employment in a rapidly transforming workplace, or a mid-career professional whose job may soon change or disappear with increasing automation, this book is for you. If you are a consultant, coach, mentor or trainer, looking for new ideas and approaches, this book will provide valuable guidelines. If you are a seasoned professional navigating the new norms, you will also find many inspiring insights"--
Keywords: Decision making -- Social aspects; Organizational change; COVID-19 Pandemic, 2020- -- Social aspects; COVID-19 Pandemic, 2020- -- Economic aspects; BUSINESS & ECONOMICS / Human Resources & Personnel Management